Implementation of a roadmap for the comprehensive diagnosis, follow-up, and research of childhood leukemias in vulnerable regions of Mexico: results from the PRONAII Strategy - Núñez-Enríquez, Juan Carlos; Romo-Rodríguez, Rubí; Gaspar-Mendoza, Pedro; Zamora-Herrera, Gabriela; Torres-Pineda, Lizeth; Amador-Cardoso, Jiovanni; López-Blanco, Jebea A.; Alfaro-Hernández, Laura; López-García, Lucero; Rosas-Cruz, Arely; Alberto-Aguilar, Dulce Rosario; Trejo-Pichardo, César Omar; et al. (Frontiers in Oncology, 2024)
The main objective of the National Project for Research and Incidence of Childhood Leukemias is to reduce early mortality rates for these neoplasms in the vulnerable regions of Mexico. This project was conducted in the states of Oaxaca, Puebla, and Tlaxcala. A key strategy of the project is the implementation of an effective roadmap to ensure that leukemia patients are the target of maximum benefit of interdisciplinary collaboration between researchers, clinicians, surveyors, and laboratories. This strategy guarantees the comprehensive management of diagnosis and follow-up samples of pediatric patients with leukemia, centralizing, managing, and analyzing the information collected. Additionally, it allows for a precise diagnosis and monitoring of the disease through immunophenotype and measurable residual disease (MRD) studies, enhancing research and supporting informed clinical decisions for the first time in these regions through a population-based study. This initiative has significantly improved the diagnostic capacity of leukemia in girls, boys, and adolescents in the regions of Oaxaca, Puebla, and Tlaxcala, providing comprehensive, high-quality care with full coverage in the region. Likewise, it has strengthened collaboration between health institutions, researchers, and professionals in the sector, which contributes to reducing the impact of the disease on the community.